2021
DOI: 10.1186/s40104-020-00538-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth restriction alters nutrient metabolism in the intestine of porcine offspring

Abstract: Background Intrauterine growth restriction (IUGR) has negative impacts on the postnatal survival, growth and development of humans and animals, with not only on newborns but also adulthood. However, the characteristics for nutrient digestion and absorption in IUGR offspring are still largely unknown. Therefore, the normal birth weight (NBW) and IUGR growing pigs were used in this study to investigate their differences in nutrient utilization, with an expectition for further nutritional optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The SI of LBW piglets is developmentally and functionally compromised compared to NBW individuals [ 63 , 64 ]. Oral Gln supplementation has been previously shown to be beneficial for the jejunal development and function of piglets around weaning [ 34 , 35 ], however only few studies examined effects of Gln supplementation in piglets during the suckling phase [ 33 , 38 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SI of LBW piglets is developmentally and functionally compromised compared to NBW individuals [ 63 , 64 ]. Oral Gln supplementation has been previously shown to be beneficial for the jejunal development and function of piglets around weaning [ 34 , 35 ], however only few studies examined effects of Gln supplementation in piglets during the suckling phase [ 33 , 38 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine growth restricted (IUGR) newborns are defined as small-sized individuals with weights below the 10th-centile for their gestational age or the population mean minus 2 standard deviations of a population-based nomogram, and their occurrence is an important problem in animal husbandry ( Dong et al., 2014 ; Li et al., 2021 ). This growth restriction exerts a permanent stunting effect on the efficiency of nutrient utilization in posterity and impairs their long-term health ( Xu et al., 2016 ; Zhang et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the downregulation of the nutrient transport gene ( SLC39A4 ) of Zn, considered as the major intracellular Zn transporter ( Martin et al, 2013 ), may be involved in the changes observed in other physiological genes that need Zn for their proper expression ( Suttle, 2010 ). Considering that the small intestine plays an essential role not only in diet digestion and nutrient absorption but also in immune response, this reduced gene expression observed in piglets of light birthweight may seriously compromise immunity functionality, as previously noted ( Michiels et al, 2013 ; Qi et al, 2019 ; Li et al, 2021 ). Indeed, a decreased development of gastrointestinal tract (e.g., length, weight, and secretory capacity), even after 18 to 28 d post-weaning, has been observed in piglets with light birthweight compared to their average birth weight littermates (912 g vs. 1,287 g BW; Michiels et al, 2013 ).…”
Section: Discussionmentioning
confidence: 52%